Flash Flood Warning Sub-Systems for Rural Africa - N. Mbau, Stella; Thiruchelvam, Vinesh (International Journal of Engineering and Technology, 2018)
This paper aims to present the need for sub-systems in rural Africa for real-time warning delivery. It has been reported in previous studies, that Sub-Sahara Africa lacks weather radars. This means that there are no real-time early warnings presenting a gap in knowledge that this study aims to address. This is done through the following objective; to examine the relationship between variables in the study and therefore, establish whether sub-systems are a significant variable in flash flood warning systems for rural Africa. The variables to be examined are; the independent variable (existing warning system), the dependent variable (early warnings), the moderator variable (ancillary elements) and the mediator variable (sub-systems). This is investigated through a closed-ended questionnaire that is administered to a sample of meteorologists whose email addresses are available on the World Meteorological Organization’s expert database. The target sample is determined through the G*Power application. The data is analyzed on SPSS. Variables in the study are found to be correlated after conducting a Pearson’s correlation test. Using PROCESS allows for the testing of various models where moderation is confirmed. A moderated mediation model is also confirmed. The results confirm that sub-systems are significant enough to be developed for rural Africa.